(3GdQSGdI GdTgGHjI aj GdUfGYGJ GdWHjIs ((3Ydi Hf YHO Gddg GdeShQi GdedbH HGdHhgej s)
(3ChdgG (B:s
(3hHYO , agPg , QSGdI eHGQcI aj UfGYI GdWH hSejJgG HGdQSGdI GdTgGHjI ai GdUfGYGJ GdWHjI(B: s
(3BNQgG (B:s
(3eHJhQ , hGdeHJhQ ebOGQ HGHjf , hBNQ GdehLhO CKfGA (B"(3GdHGH hGdSHYhf(B" (3bhdg (B: (3GdeSCdI GdKGdKI YTQI , ce gi CbSGe Gdbhi ? GdLhGH (B: (3KdGKI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHYs
(3eTJedI Ydi KeGfjf HGHkG ai GdJOGhjs
(3hfcJ fhGOQ ef GdeYGdLGJs
(3HChdgG agQSJ ddehVhYGJs
(3hcJHJ GdYfGhjf HGdMeQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdWHs